Peran Partai Politik dalam Menggerakkan Partisipasi Politik Rakyat - Hasanudin (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2018)
Political participation is a citizen activity that acts as individuals intended to influence government decision making. Participation can be individual or collective, organized or spontaneous, peaceful or violent, legal or illegal, effective or ineffective. In general, Political Parties have a role as a means of political communication, the party plays a very important role in an effort to articulate interests or “political interests” that are hidden or sometimes hidden in society and combine with other political interests (political agrigation) . Second, the Party as a means of political socialization. Political parties also play a role as a means of political socialization (instrument of political socialization). Third, political parties are a means of political recruitment. fourth, is the regulator and manager of conflicts that occur in the community (conflict management). There are several variables that can be used to explain why political participation is important, some of which are; (1) Political trust; (2) socio-economic status; (3) Personality or psychological explanation.